The Excessive Sportivization of Physical Education Lessons on the Gymnasium School Level - A. Rosca; D.I. Tohanean (Editura Universitatii Transilvania din Brasov, 2022)
This paper presents an analysis of the physical education class at the gymnasium level from the perspective of the eventual excess of sports content and the effects of this aspect. The school curriculum at this level was analyzed and questionnaires were applied to some teachers and students to identify their opinions on the previously mentioned theme. The general conclusion that emerged from this study was that, indeed, sports-type contents are the majority (over 80% in each class), and the teachers seem to agree with this structure. The opinion of the students is not unified; approximately half feel various aspects that make them reserved regarding the pleasure of participating in these physical education classes.